Antibacterial activity of honey in preserving high-pressure cooked milkfish stored at room temperature. (February 2019) - Hakim, D A; Tjahjaningsih, W; Sudarno,
Abstract: High-pressure cooked milkfish is susceptible to decay during the storage process at room temperature because it has a relatively high water and protein content. The use of honey as a natural preservative containing antibacterial compounds is expected to improve the quality and shelf life of high-pressure cooked milkfish. This study aims to determine the effect of honey as a natural preservative against the total amount bacteria and organoleptic value during storage at room temperature. The treatment in this study was the use of a honey solution concentration as the preservative using samples consisting of 0% (without honey or control), 20%, 25%, 30% and 0.1% sodium benzoate solution. The results showed that the concentration of 30% for the honey solution was able to maintain the quality of the high- pressure cooked milkfish during storage at room temperature for up to 72 hours with the total bacteria being 2, 3x10 5 colonies/gram (< 5, 0x10 5 colonies/gram) with an average organoleptic value of 7, 45.